Use of an Affective Teaching Intervention to Impact Connections Between Academic and Professional Integrity - Morrill, Deborah (Southern Connecticut State University, 2021)
Dishonesty and misconduct of nursing students during their education is a continuing concern, especially as it relates to expected professional behaviors. This quasi experimental pre-and post-interventional study explored the impact of an affective learning module on developing beliefs and perceptions of ethicality of academic and professional misconduct of students in a BSN program. A modified version of McCrink’s (2008) tool, entitled “Nursing Student Experiences and Perceptions of Academic and Professional Conduct Survey” measured these constructs. The affective learning module, based on Rest’s theory of moral development, and Krathwohl’s affective taxonomy, actively engaged students in ethical decision-making with connections to professional practice through discussion, case review and reflection. The pretest data (N=65) analysis using Mann Whitney U, indicated differences in mean rank related to enrollment status, healthcare work experience and gender and beliefs, and perceptions of academic and professional misconduct. A comparative analysis (N=16) of pre and posttest data was limited due to required changes related to the COVID-19 pandemic. Changes in pre and posttest data suggest the need to replicate and continue research in the area of intentional affective teaching of ethicality and professional values.
Keywords: Affective domain; Affective taxonomy; Dishonesty; Integrity; Misconduct; Value development; dept.nur